Synthesis and characterization of marine seagrass (Cymodocea serrulata) mediated titanium dioxide nanoparticles for antibacterial, antibiofilm and antioxidant properties - Narayanan M.; Srinivasan S.; Gnanasekaran C.; Ramachandran G.; Chelliah C.K.; Rajivgandhi G.; Maruthupandy M.; Quero F.; Li W.-J.; Hayder G.; Khaled J.M.; Arunachalam A.; et al. (Academic Press, 2025)
Cymodocea serrulata mediated titanium dioxide nanoparticles (TiO2 NPs) were successfully synthesized. The XRD pattern and FTIR spectra demonstrated the crystalline structure of TiO2 NPs and the presence of phenols, flavonoids and alkaloids in the extract. Further SEM revealed that TiO2 NPs has uniform structure and spherical in shape with their size ranged from 58 to 117 nm. Antibacterial activity of TiO2 NPs against methicillin-resistant Staphylococcus aureus (MRSA) and Vibrio cholerae (V. cholerae), provided the zone of inhibition of 33.9 1.7 and 36.3 1.9 mm, respectively at 100 ?g/mL concentration. MIC of TiO2 NPs against MRSA and V. cholerae showed 84% and 87% inhibition at 180 ?g/mL and 160 ?g/mL respectively. Subsequently, the sub-MIC of V. cholerae demonstrated minimal or no impact on bacterial growth at concentration of 42.5 ?g/mL concentration. In addition, TiO2 NPs exhibited their ability to inhibit the biofilm forming V. cholerae which caused distinct morphological and intercellular damages analysed using CLSM and TEM. The antioxidant properties of TiO2 NPs were demonstrated through TAA and DPPH assays and exposed its scavenging activity with IC50 value of 36.42 and 68.85 ?g/mL which denotes its valuable antioxidant properties with potential health benefits. Importantly, the brine shrimp based lethality experiment yielded a low cytotoxic effect with 13% mortality at 100 ?g/mL. In conclusion, the multifaceted attributes of C. serrulata mediated TiO2 NPs encompassed the antibacterial, antioxidant and anti-biofilm inhibition effects with low cytotoxicity in nature were highlighted in this study and proved the bioderived TiO2 NPs could be used as a promising agent for biomedical applications. ? 2024 Elsevier Ltd